Alpha-Fetoprotein-Producing Lung Hepatoid Adenocarcinoma with Brain Metastasis Treated with S-1 - Muroyama, Yuki; Tamiya, Hiroyuki; Tanaka, Goh; Tanaka, Wakae; Huang, Alexander C.; Oldridge, Derek A.; Matsusaka, Keisuke; Takazawa, Yutaka; Jo, Taisuke; Ushiku, Tetsuo; Nagase, Takahide (Case reports in oncology, 2020)
Lung hepatoid adenocarcinoma (HAC) is a rare primary lung carcinoma pathologically characterized by hepatocellular carcinoma-like tumor cells, the majority of which produce alpha-fetoprotein (AFP). The clinical prognosis of lung HAC is generally poor, and effective therapeutic regimens for inoperable or recurrent cases have not been established. Here, we report a case of AFP-producing lung HAC with brain metastasis with long-term disease control, treated with the 5-fluorouracil-derived regimen S-1. The patient was a 66-year-old male admitted to the hospital with alexia. Chest X-ray revealed a massive tumor in the left upper lobe, and a head CT scan revealed a metastasis in the left parietal lobe. The laboratory data showed a remarkably elevated AFP level (97,561 ng/mL). Pathological assessment of the resected brain tumor revealed HAC, which was compatible with the lung biopsies. Together with the absence of other metastatic lesions, a final diagnosis of primary lung HAC, stage IV T4N3M1b, was given. The patient first underwent non-small cell lung cancer chemotherapy regimens (carboplatin and paclitaxel as the first line, and pemetrexed as the second line), but had clinical progression. After third-line oral S-1 (tegafur/gimeracil/oteracil) administration, the serum AFP level significantly dropped and the patient achieved long-term disease control without relapse, surviving more than 19 months after disease presentation. The autopsy result was consistent with the diagnosis of primary lung HAC, and immunohistochemical staining was AFP+, glypican 3+, and spalt-like transcription factor 4+. Here, we report the case of a rare primary lung HAC with apparent disease control on S-1 therapy, together with a literature review.